The strategic value of servitization: A quality management perspective. Issue 4 (2nd October 2021) - Erkul, Muratcan; Chakraborty, Subhajit; Kaynak, Hale
Abstract: We propose a typology suggesting varying extent of servitization for manufacturing firms in different industries that could help them improve their firm performance. We suggest that contemporary manufacturing firms may benefit from implementing quality management practices while being organizationally innovative and staying focused on satisfying their customer needs. Cluster analysis and MANOVA on a cross-country sample of senior managers in charge of quality implementation at various manufacturing firms demonstrated the presence of very high and low servitizers, enjoying high and low firm performance respectively, thereby providing empirical support for our typology. Manufacturing firms can implement the proposed servitization strategies to improve their performance. Research and practice implications are discussed and future directions are offered.